Applied imagination - Finn, Ed; Torrejon Capurro, Carolina; Bennett, Michael G.; Wylie, Ruth (Frontiers in Psychology, 2023)
Imagination is a fundamental human capacity, and to navigate our current global challenges, we need to define and encourage the practice of imagination, or what we term "applied imagination." In this study, we convened a series of focus groups or "virtual salons" to address three guiding questions:(1) How might we define imagination? (2) How might we (or should we) measure imagination? and (3) How might we foster imagination? Our efforts to define applied imagination highlight the crucial role imagination plays in human survival and thriving, and the role of social forces in fostering or discouraging imagination, the connection between imagination and faith, and the "dark side" or maladaptive aspects of imagination. The discussions on measuring imagination were quite divided, with some salon participants arguing for the potential of indirect modes for measuring imaginative capacity while others argued that measuring imagination was functionally impossible and morally suspect. Finally, our results around fostering imagination suggest the importance of using play and humor, separating imaginative activities from the everyday, and employing constraints to prompt imaginative responses. We end with a discussion of possible directions for future research and a call to create a transdisciplinary field of imagination studies.